A structure-based mechanism of cisplatin resistance mediated by glutathione transferase P1-1 - De Luca, Anastasia (Proc Natl Acad Sci U S A, 2019)
Cisplatin [cis-diamminedichloroplatinum(II) (cis-DDP)] is one of the most successful anticancer agents effective against a wide range of solid tumors. However, its use is restricted by side effects and/or by intrinsic or acquired drug resistance. Here, we probed the role of glutathione transferase (GST) P1-1, an antiapoptotic protein often overexpressed in drug-resistant tumors, as a cis-DDP–binding protein. Our results show that cis-DDP is not a substrate for the glutathione (GSH) transferase activity of GST P1-1. Instead, GST P1-1 sequesters and inactivates cisplatin with the aid of 2 solvent-accessible cysteines, resulting in protein subunits cross-linking, while maintaining its GSH-conjugation activity. Furthermore, it is well known that GST P1-1 binding to the c-Jun N-terminal kinase (JNK) inhibits JNK phosphorylation, which is required for downstream apoptosis signaling. Thus, in turn, GST P1-1 overexpression and Pt-induced subunit cross-linking could modulate JNK apoptotic signaling, further confirming the role of GST P1-1 as an antiapoptotic protein.